An Implementation of Quantum Learning Model to Improve Social Attitude and History Subject Learning Result of XI IPS 2 Students at SMAN Plus Sukowono - Dyah Ayu Safitri; Mohammad Na'im; Sri Handayani (JURNAL HISTORICA, 2017)
The use of information technology has brought negative effects for students. Nowdays, students have less interaction with people and act anti-socially. The first analysis of students’ social attitude by using 5 indicators are tolerating , cooperating, social care, sense of brotherhood, and appreciating achievement achieved the minimimun score showed that the result was 34,7%.The learning achievemectnt incognitive domain was 22%. Trough this study, it is expected that the use of Quantum Learning model will improve students’ social attitude and learning result. This classroom action research uses Hopkins model and qualitative and quantitative approach. This research was done in three cycles with 22 students as the subjects. The data collection methods used in this research were observation, questionnaire, essay test, interview, and documentation. It was found that the average percenatges of students’ social attitude were 34,7% in pre-cycle and 52,46% in cycle 1. It increased as much as 17% and became 71,32% in cycle 2. In cycle 3, the average percentage increased as much as 3,4% and became 79%. Students’ learning result was measured through tests on cognitive aspects that were done at the end of each cycle. The percentage of students’ learning achievement were 22% in pre-cycle, 45,4% in cycle 1, and 59,09% in cycle 2. In the third cycle, the percentage increased and became86,3%.These results show that through this research, students social attitude and learning results were improved with Implementation of Quantum Learning Model. Keywords: Quantum Learning, social attitude, students' learning result